Comparative Antioxidant and Phytochemical Evaluation of Selected Varieties of Colocasia esculenta (L.) Schott Leaves (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Sree Kiran, Sree Rashmi, Sree Pallavi, and Muktakeshi are the four commonly cultivated varieties of Colocasia esculenta (L.) Schott. The current study aims to perform phytochemical screening and the antioxidant capacity of the leaf extracts of these varieties. Furthermore, LCMS was used to examine the polyphenolic content of Muktakeshi's ethanolic leaf extract. The phytochemical analysis of the cultivars indicated that all extracts contained beneficial phytocompounds like phenols, terpenoids, flavonoids, alkaloids, saponins, and tannins. The ethanolic leaf extract of Muktakeshi was found to have greater levels of total phenol (39.47±0.47 GAE mg/g) and flavonoid (49.672±0.15 QE mg/g) contents. All the leaf extracts exhibited a moderate antioxidant ability, whereas the ethanolic extract of Muktakeshi exhibited comparatively higher antioxidant potential in both DPPH (88.3±0.58%) and nitric oxide (84.6±0.79%) assays with the least IC50 value. The LCMS studies detected eight polyphenolic compounds like quercetin, kaempferol, gallic acid, caffeic acid, luteolin 7-rutinoside, chlorogenic acid, vitexin, and rutin in the ethanolic leaf extract of Muktakeshi. It is a good source of many potentially effective bioactive compounds and helps to prevent human oxidative stress-associated diseases. The present study found considerable variations in the phenol-flavonoid content and antioxidant properties of the Colocasia varieties studied.